Case report: Approaches to treatment-refractory and super-refractory glutamic acid decarboxylase antibody-spectrum disorders - Rajmohan, Ravi; Baveja, Shivali; Nguyen, Dai; Shah, Eshita; Sy, Michael; Attaripour, Sanaz; Swope, David (Frontiers in Immunology, 2024)
Background: GAD antibody-spectrum disorders (GAD-SDs) include a group of autoimmune neurological diseases associated with neuronal excitability, most noticeably stiff person syndrome. Immune modulators are the mainstay of treatment, but a significant number of patients remain refractory. Methods: We present our single-center experience of 8 cases of GAD-SD, 2 of which were refractory to immune modulatory treatments. Results: Of the 2 cases refractory to immunomodulation, one had significant improvement with bilateral Globus Pallidus interna deep brain stimulation (GPi DBS) placement and the other with autologous hematopoietic stem cell transplant (aHSCT). Discussion: To our knowledge, this is the first instance of GPi DBS placement being noted to improve GAD-SDs movements.